Improving Boyolali Regency Community Understanding of Pressure Swing Adsorption (PSA) Technology and The Use of Efficient Adsorbents - Susilo, Bambang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
Boyolali Regency produces large amounts of organic waste from extensive livestock farming, particularly cow dung, which can be converted into biogas. However, biogas quality is reduced by carbon dioxide (CO₂) impurities. This study introduced and assessed Pressure Swing Adsorption (PSA) technology to improve biogas quality in five districts of Boyolali. Activities included surveys, educational sessions, mentoring, and PSA system evaluation. Surveys showed limited community knowledge of PSA technology. After four educational sessions and mentoring, participants demonstrated increased understanding and interest, supported by pre-test and post-test results. The PSA system was successfully used to power household appliances, proving its feasibility. Challenges remain, such as short operational times (15 seconds at 2.2–1.8 bar pressure) and high costs. The findings indicate PSA technology's potential as a renewable energy solution but highlight the need for further development and community involvement for sustainable implementation.